Self-management of diabetes in children and young adults using technology and smartphone applications. - Sheehy, S; Cohen, G; Owen, K (2014)
Treatment compliance and adherence are often a challenge in patients with type 1 diabetes, particularly for adolescent and young adult patients. With the availability of the internet and smart phone applications (apps) there is a hope that such technology could provide a means to encourage treatment adherence in this group of patients. This review focuses on whether telemedicine and smartphone technology in diabetes can influence self-management in young people with diabetes. A large number of smartphone apps are targeted at people with diabetes, but a limited number of well designed evaluation studies have been performed. As our review shows, the evidence base for efficacy of most of these applications is minimal and improvement in hard outcomes such as HbA1c and complication development is largely lacking.